ІДЕОЛОГІЯ МОНОЛІНГВІЗМУ І БІЛІНГВІЗМУ В ПОЛІКУЛЬТУРНІЙ ОСВІТНІЙ ПОЛІТИЦІ США - Бахов, Іван (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті вирішується завдання здійснення аналізу політиким монолінгвізму на противагу політиці білінгвізму в мовній політиці США. На основі теоретичного аналізу джерел розглядаються історичні передумови, проблеми та механізми реалізації політики монолінгвізму в поліетнічній державі, результат якої спрямований проти культурного різноманіття іммігрантських та міноритарних мов. Зроблено висновок про поведінкову і мовну асиміляцію іммігрантів як неминучу складову культурної асиміляції в домінуюче суспільство в результаті визнання англійської мови мовою рівних можливостей. В статье решается задача осуществления анализа политики монолингвизма в противовес политике билингвизма в языковой политике США. На основе теоретического анализа источников рассматриваются исторические предпосылки, проблемы и механизмы реализации политики монолингвизма в полиэтническом государстве, результат которой направлен против культурного многообразия иммигрантских и миноритарных языков. Сделан вывод о поведенческой и языковой ассимиляции иммигрантов как неизбежной составляющей культурной ассимиляции в доминирующее общество в результате признания английского языка языком равных возможностей. The article analyzes the monolingualism policy opposed to the policy of bilingualism in the language policy of the United States. The author considers the historical background, issues and implementation mechanisms of the monolingualism policy in the multiethnic state, the result of which is directed against cultural diversity and immigrant minority languages. The article defines sources of English monolingualism ideology, racial hostility of majority toward minority, ethnic conflict between the minorities, class antagonism of socioeconomic groups at a lower level of welfare; political negative reaction of bilingualism opponents; negative attitude to everything that is foreign. The author presents arguments and counterarguments used by bilingualism supporters and linguistic diversity in the United States. Federal policy bilingual education is compared with the American melting pot. Behavioral and linguistic assimilation of immigrants is presented as an inevitable component of cultural assimilation into the dominant society resulting from the recognition of English as the language of equal opportunities.